Peran Love of Money, Self-Esteem, dan Gender pada Persepsi Etis (Studi pada Mahasiswa Akuntansi Generasi Z) - Astungkara, Agni; Rois, Dimas Ilham Nur; Kurniati, Sari; Dewangga, Wimbi Praska (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2024)
Numerous initiatives have been made to mitigate fraud in the business community. Ethical considerations are critical in executing this step. Initializing with attempts to raise ethical awareness, ethical perception in addition ending with the implementation of ethical business practices. This study investigates the effects of love of money, self-esteem, and gender on accounting students' ethical perception. The data obtained by survey method, and the data processing method is Multiple Regression Analysis. Taking 99 samples of Accounting students from Generation Z, the findings reveal that love of money has a negative impact on student’s ethical perception. Self-esteem and gender differences have no effect on ethical perceptions. The results of the moderation test showed that self-esteem moderates the relationship between gender and ethical perceptions, but unable to moderate the relationship between love of money and ethical perceptions.